Epidemiology of Burn-Related Morbidity and Mortality in Patients Over 80 Years of Age - Secanho, Murilo Sagrbi [UNESP] (2022)
Burns cause greater morbidity and mortality in older patients owing to the physiological changes and functional status declines with age. We sought to characterize the epidemiology of burn injuries in the patient population aged over 80 years. A retrospective analysis of all patients aged >80 years admitted to a tertiary burn center in Brazil over a 10-year period was conducted. Multiple parameters including comorbidities, BSA burned, intensive care unit (ICU) admissions, inhalation injury, and revised Baux score were analyzed to assess association with mortality. Twenty-six patients were identified. The overall mortality rate was 42.3%. The mortality rate increased with the TBSA, with 100% mortality at >20% total BSA involvement (P < .001). Inhalation injury occurred in 3 (11.5%) patients, all of whom suffered mortality (P < .001). ICU admission was necessary for 14 (53.8%) patients, out of which 11 (78.6%) did not survive (P < .001). The revised Baux score had a significant impact on the mortality, with higher values among patients who did not survive (89.2 ± 6.2 vs 110.7 ± 17.9, P < .001). Burns cause high mortality in the octogenarian and nonagenarian populations. It is important to stratify patients at high risk, institute prompt treatment and discuss goals of care early on for optimal patient outcomes.